International financial transmission of the Fed's monetary policy - Nikola Mirkov (International Journal of Economic Sciences and Applied Research, 2014)
This paper proposes a way to study the transmission mechanism of the US monetary policy to foreign yield curves. It elaborates the high-frequency identification of monetary policy shocks from (Piazzesi, 2005) in an international setting. The shocks are extracted from a two-country term structure model and the procedure is illustrated on the US-UK daily data.
Keywords: E43; E52; G12; 330; term premia; Fed; policy actions